Protecting Temporary Workers : Migrant Welfare Funds from Developing Countries - Ruiz, Neil G. (World Bank, Washington, DC, 2012)
This brief provides an overview and lessons on how countries of origin governments can play a major role in protecting their migrants abroad through migrant welfare funds. It draws from a study by the Migration Policy Institute, on the Philippine Overseas Workers Welfare Administration (OWWA), a US$172 million government-operated welfare fund that is funded by a mandatory US$25 membership fee for departing Overseas Filipino Workers (OFWs). The Philippine experience shows that a welfare fund has to: (1) find the right balance of services; (2) create meaningful partnerships; (3) build accountability with its members; and (4) actively involve destination countries.